If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 11X = 0 Reorder the terms: 11X + y = 0 Solving 11X + y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1y' to each side of the equation. 11X + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 11X + 0 = 0 + -1y 11X = 0 + -1y Remove the zero: 11X = -1y Divide each side by '11'. X = -0.09090909091y Simplifying X = -0.09090909091y
| 5-6n^2=-19 | | 0.6+z=30 | | -5x+4x+6=21 | | 1.80=1+0.05*12 | | (10x+2)2=(15x+19) | | 17x+8+11x+4=180 | | 1.80=1+0.05x | | 8/15/n=2/3 | | 5(4+3x)-9=-31 | | 2x^2-30x=-5x^2-3x-18 | | s+9=-27 | | 2.1x+4.2y=14.7 | | 2*4x*3y-4x+7y= | | 10/2420/24 | | (6x-55)=(3x-16) | | (X+3)(2x-8)= | | 7a^2+64a+64=0 | | 5(4+3x)-9=31 | | 4x^2=620 | | 12x(x-20)=-48 | | 2p^2-10p+9=0 | | (7x-6)=(3x+14) | | 6x^2+6x-14=49-41x | | 4=6/(2x-3) | | 8(3x+1)=1 | | (10+8v)-10=-72 | | Y/7=17/3 | | x^2+4x+y^2=-3 | | t=2s-1 | | 8m^3n-40m^2n^2+56mn= | | Bs=66 | | x^4-7x^3+2x^2+28x-24=0 |